2012
DOI: 10.5601/jelem.2013.18.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium on animal health

Abstract: Selenium is an essential trace element in the diet of humans and domesticated animals. It is a component of more than 30 selenoproteins, which play a significant role in the body. Selenoproteins protect cells from damage inflicted by free radicals, the cause of many chronic diseases. They also participate in the metabolism of thyroid hormones, control reproductive functions and exert neuroprotective effects. In addition to its anti-proliferative and anti-inflammatory properties, selenium stimulates the immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 53 publications
(41 reference statements)
1
23
0
2
Order By: Relevance
“…In general, buffalo calves produced from G 4 recorded the highest (P<0.05) values of TP, AL, T 3 , T 4 , Se and GL as well as activities of GSH and SOD enzymes and the lowest (P<0.05) values of ALT and AST as compared to those of G 1 or G 2 and G 3 , respectively. This finding came in agreement with previous reports by Pechova et al (2012) and Zarczynska et al (2013). The observed enhancement in TP and AL concentrations in plasma of calf delivered from dams treated with (G 2 , G 3 and G 4 ) may be attributed to higher increase in TP and AL concentrations or an increase of Se and glucose levels in plasma of their dams, particularly in G 4 (Table 2).…”
Section: Blood Constituents Of Calvessupporting
confidence: 93%
See 1 more Smart Citation
“…In general, buffalo calves produced from G 4 recorded the highest (P<0.05) values of TP, AL, T 3 , T 4 , Se and GL as well as activities of GSH and SOD enzymes and the lowest (P<0.05) values of ALT and AST as compared to those of G 1 or G 2 and G 3 , respectively. This finding came in agreement with previous reports by Pechova et al (2012) and Zarczynska et al (2013). The observed enhancement in TP and AL concentrations in plasma of calf delivered from dams treated with (G 2 , G 3 and G 4 ) may be attributed to higher increase in TP and AL concentrations or an increase of Se and glucose levels in plasma of their dams, particularly in G 4 (Table 2).…”
Section: Blood Constituents Of Calvessupporting
confidence: 93%
“…Selenomethionine supplementation of goats from six weeks before delivery significantly enhanced selenium and total protein levels in plasma of their kids (Pechova et al, 2012). Also, Zarczynska et al (2013) demonstrated that selenomethionine can be incorporated into GSH, which helps to protect all body cells from free radicals which are produced during normal metabolic activities and also be incorporated in other proteins in substitution for methionine. Moreover, Schrauzer and Surai (2009) indicated that selenomethionine is the only naturally occurring Se compound that is significantly incorporated into body proteins.…”
Section: Blood Constituents Of Calvesmentioning
confidence: 94%
“…The disease involves hyaline degeneration of muscle cells in various skeletal muscles, including the diaphragm and the heart [ 204 ]. In ruminants, WMD is also manifested by changes in the frequency and quality of heartbeat [ 205 ]. In lambs with WMD, the arrhythmia was diagnosed using electrocardiography (ECG) [ 206 ].…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%
“…The arrhythmia is observed at early stages of cardiomyopathy. The electrocardiograms of diseased calves revealed elevated heart rate, accelerated sinus rhythm, increased P wave amplitude, shorter PR, QT and ST interval, narrower QRS complex, shorter T wave duration and insignificantly increased T wave amplitude [ 205 ].…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%
“…As an essential trace element, selenium (Se) can enhance immunity, anti-oxidation, and anti-cancer capacity of human and animals. The deficiency of Se may lead to muscular dystrophy, exudative diathesis, necrotic liver degeneration, and mulberry heart disease in farm animals [ 1 ]. On the other hand, high dose of Se can cause selenosis in swine involving hair loss, cracking of hooves, and an interruption in coronary band development of the hoof [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%